The grease of the wheel: The correlation between corruption, regional revenue and expenditure in Indonesia - Sanda Aditiya Arsandi (Komisi Pemberantasan Korupsi, 2022)
Previous research has revealed that corruption is considered to have two types of effects on the economy. Corruption is seen as an obstacle to the economy but also as a